Oficina de música com pacientes renais hospitalizados: uma proposta de trabalho para o psicólogo hospitalar - Roth, Maria Cecilia (2009)
Hospital psychology in Brazil started with the work of psychologists who began their activities as auxiliary to medical diagnosis. Thereafter, psychologists have gradually tried to define and understand their role together with patients who were hospitalized. Identifying psychological demand, in the presence of disease, has been a challenge for psychologists accustomed to the therapeutic setting of the clinic. Working and communicating with a multidisciplinary team, as well as understanding the dynamics of the hospital, has created new challenges for the hospital psychologist. Similarly, finding a new approach for the patient has required a deconstruction of the most traditional methods, as the merely verbal approach may be impossible since this patient is often unable to communicate verbally. Several studies, particularly with children, try to introduce new resources to the approach of the hospital patient such as music and visual arts (Oaklander) and play therapy ( Lindquist). As the number of professional psychologists is still small vis a vis the number of patients who could benefit from this assistance, developing other ways to deal with hospitalized patients becomes necessary. Tthe objectives of this research were to discuss how the music workshop may become a working resource of the hospital psychologist and how the participation of hospitalized patients with chronic kidney disease in the music workshop may facilitate the expression of meaningful life experiences. The research was developed in a specialization hospital located in the city of São Paulo with patients hospitalized for chronic kidney disease. The workshop was held twice a week for a period of 18 months in the corridor of the hospital. it was conducted by two musician-psychologists that played hillbilly guitar and guitar. The songs played were requested by the patients themselves. Five patients were interviewed (four men and one woman ), three of which had undergone a transplant some time before, one had just undergone a transplant and the last was still undergoing hemodialysis treatment. the interviews were done immediately after their participation in the workshop. in order to understand and discuss the patients experience of becoming sick we used concepts of the philosopher Martin Heidegger and followers as a theoretical reference. The main focus in analyzing the interviews was the way each interviewee dealt with his being ill . At the end of the research we were able to discuss the music workshop as a resource for hospital psychologists and what having participated in this workshop meant to the patients